Motivasi Petani Dalam Berusahatani Bunga Mawar Di Desa Karangpring Kecamatan Sukorambi Kabupaten Jember Jawa Timur - Yova Yunizar Desy; Sri Subekti; Sofia Sofia; Rokhani Rokhani (Universitas Sebelas Maret, 2026)
Floriculture is a horticultural sub-sector with high economic value and significant potential to increase farmers’ income. Rose cultivation is one of the main sources of livelihood for the community in Karangpring Village, Sukorambi District, Jember Regency. This farming activity has been carried out for generations and serves as a key support for farmers’ household economy. This study aims to measure the level of farmers’ motivation and to analyze the factors associated with farmers’ motivation in rose farming. The research was conducted in Karangpring Village, Sukorambi District, using a quantitative descriptive method. The population consisted of 129 farmers, with a sample of 34 respondents selected randomly using a simple random sampling technique. Data were collected through observation, interviews, and documentation. The data were analyzed using Spearman’s rank correlation.The results show that the level of farmers’ motivation in rose farming is in the moderate category. Farmers stated that the cultivation process of roses is relatively easy; however, the income obtained is not yet stable due to price fluctuations, as well as limited support and assistance from agricultural extension workers. Factors significantly associated with farmers’ motivation include age, farming experience, and the frequency of participation in extension activities. Meanwhile, formal education and land size are not significantly associated with farmers’ motivation.